Evaluation of Aspects of Continuing Nursing Education Programs in Kirkuk Health Directorate Hospitals - Hussein M. Abdulfatah1 , Salma K. Geehad2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): To evaluate the aspects of the Continuing Nursing Education Programs in Kirkuk Health Directorate Hospitals Methodology: A descriptive design, using self-evaluation approach, is employed throughout the present study. A non-probability sample of (251) staff nurse are recruited from Kirkuk Health Directorate Hospitals; Kirkuk General Hospital and Azady Hospital. A questionnaire is constructed for the purpose of the study which comprised of (1) part, (6) aspects and (52) item. Content validity and internal consistency reliability are determined for the questionnaire through a pilot study. Data are collected through the use of the questionnaire and structured interview a means of data collection. Data are analyzed through the application of descriptive statistical data analysis approach of frequency, percentage, mean of scores, total scores and range. Results: The study indicates that the majority of nurses have evaluated the aspects of the continuing nursing education program as poor at Kirkuk Health Directorate. Conclusion: The study concludes that the evaluation of aspects of the continuing nursing education programs is appraised as poor for the majority of nurses’ self-evaluation. Recommendations: The study recommends that mandatory, periodic, systematic and effective evaluation of continuing nursing education program can be carried out for the benefit of both staff nurses, these programs and the quality of nursing care. Further research can be carried out on a large sample size, varied range scale of variables, large sample size and nation-wide continuing nursing education programs.